Deep‐sea nodules versus land ores: A comparative systems analysis of mining and processing wastes for battery‐metal supply chains. (13th January 2022) - Paulikas, Daina; Katona, Steven; Ilves, Erika; Ali, Saleem H.
Abstract: To meet UN Sustainable Development goals, a clean‐energy transition with minimal ecological impact from its raw‐material supply chain is essential. Polymetallic nodules lying unattached on the abyssal seafloor of the Pacific Ocean's Clarion Clipperton Zone contain four critical metals (nickel, cobalt, manganese, copper) in large quantities, and the International Seabed Authority may soon enact regulations to allow their commercial exploitation. There are complex global ecological implications of doing so. Nodule exploitation would damage abyssal habitats and may impact midwater‐column organisms; but in the absence of nodule exploitation, terrestrial mining's environmental and social impacts would intensify. This paper adds to the growing systems‐based literature on nodule collection by contributing a preliminary material flow analysis of global‐average cradle‐to‐gate waste streams using either nodules or terrestrial sources as part of a preliminary life cycle assessment, as well as integrated risk assessments of those waste streams. System endpoints are battery precursors (nickel sulfate, cobalt sulfate, manganese sulfate), copper cathode, and a 40% or 75% manganese product. Overburden, tailings, and processing and refining wastes from terrestrial mining are compared to the nodule industry's anticipated offshore and onshore wastes, including sediment disrupted by nodule‐collection machines. Robustness to offshore technology assumptions is tested using Monte Carlo simulation, while onshore mass‐flow scenarios incorporate a "negligible‐waste" flowsheet and high‐waste flowsheets where manganese is not recovered. A billion‐EV scenario incorporates the effects of declining terrestrial copper and nickel ore grades. Results imply that metal production from nodules may produce less waste of lower severities, caveated by uncertain impacts of disrupted sediment.